The risk of contaminated ultrasound gels in the intensive care unit: lessons from an outbreak of Burkholderia cenocepacia - Beevifatimah Ahamed Sha; Paul Anantharajah Tambyah; Shi Poh Li; Sarathamani Rethenam; Lilibeth Silagan Alenton; Ling Chee Poh; Yuan Sun Yong; Peng Sii Yong; Gabriel Yan Zherong; Lasantha Ratnayake; Michelle Ang; Gerald Chua; et al. (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract